Elderly Victimization in the Context of Witchcraft Accusations and Persons Accused of Witchcraft Practices Living Within the Gambaga Witches’ Camp: Understanding of Human Rights - Onzaberigu, Nachinaab John; Ofori-Dua, Kwadwo; Dwumah, Peter; Manful, Esmeranda (Journal of victimology and victim justice (Print), 2024)
The practice of sociocultural belief systems in Ghana such as witchcraft accusations leads to situations where some elderly people in the northern part of Ghana are likely to be victimized based on sociocultural belief systems. Persons accused of witchcraft practices can be denied some of their basic fundamental human rights. The lack of a clear understanding of human rights standards among many rural folks, especially in a rural part of Northern Ghana, makes many people consider accusations of persons suspected of witchcraft practices as a non-abuse of victims’ human rights when persons accused of witchcraft are encamped in witches’ camps. Hence, this study sought to explore the accused persons of witchcraft practice’s understanding of human rights and how their conceptualization of human rights has led to elderly victimization based on sociocultural practices regarding witchcraft accusations. The study employed a qualitative method where 37 participants were selected consisting of persons accused of witchcraft practices living within the Gambaga witches’ camp. A thematic approach was used in the data analysis. The study found that accused persons of witchcraft practices have a distinctive understanding of human rights, which they conceptualized to include social and cultural rights, economic rights, civil and political rights and legal rights and missed out on the civil and political aspects of human rights. The study found that the accused persons’ lack of understanding of the civil rights concept of human rights made most of the persons living within the Gambaga witches’ camp to be victims of torture, undergo forced labour, lack their right to protection, gender discrimination and slavery within the camp. The study recommended that traditional leaders should engage in community dialogues that facilitate open and inclusive community dialogues to discuss the negative impact of witchcraft accusations on individuals and the community as a whole.